2010
DOI: 10.1148/radiol.10090320
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral, Facial, and Orbital Involvement in Erdheim-Chester Disease: CT and MR Imaging Findings

Abstract: Lesions of the brain, meninges, facial bones, and orbits are frequently observed and should be systematically sought on the brain MR and CT images obtained in patients with ECD, even if these patients are asymptomatic. Careful attention should be directed to the periarterial environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
149
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(167 citation statements)
references
References 24 publications
12
149
1
5
Order By: Relevance
“…Apart from the view of functional status of hypothalamic-infundibulo-pituitary axis, there is a report investigating the brain images in ECD patients [35]. In this report, it has been reported that hypothalamic-pituitary axis was involved in 16 (47%) of 33 ECD patients, most frequently, 14 showed loss of T1-high intensity at posterior lobe and 6 showed thickened stalk.…”
Section: Hypothalamic-pituitary Imaging In Ecdmentioning
confidence: 88%
“…Apart from the view of functional status of hypothalamic-infundibulo-pituitary axis, there is a report investigating the brain images in ECD patients [35]. In this report, it has been reported that hypothalamic-pituitary axis was involved in 16 (47%) of 33 ECD patients, most frequently, 14 showed loss of T1-high intensity at posterior lobe and 6 showed thickened stalk.…”
Section: Hypothalamic-pituitary Imaging In Ecdmentioning
confidence: 88%
“…Only three patients had normal imaging results [36], and two or more different anatomic sites were affected in most patients. Lesions are frequent in the brain, meninges, facial bones, and orbits in ECD patients.…”
Section: Cns Involvementmentioning
confidence: 96%
“…Bone scintigraphy reveals symmetrically increased radionuclide uptake at the level of the distal femoral diaphyses and metaphyses, a quite distinctive finding of the disease (E). hemispheres 30,35,36 . The dentate nucleus may show abnormal symmetric high signal intensity on T2WI that can also be found in the middle cerebellar peduncles.…”
Section: Mri Findings and Differentialmentioning
confidence: 99%
“…If the exact origin of these nongranulomatous lesions remains unknown, histological examination of these dentate nuclei lesions can be performed to reveal extensive loss of myelin sheath tissue, with gliosis and marked sparing of axons 35 . Meningeal lesions and meningioma-like mass lesions: either a single/multiple dural mass, or diffuse pachymeningeal thickening, or even both of those 32,35 . Parasellar lesions have also been reported, which may infiltrate the cavernous sinus 22 .…”
Section: Mri Findings and Differentialmentioning
confidence: 99%
See 1 more Smart Citation